Stability of non-premixed turbulent methane flames: Numerical simulations of the critical diameter and flame stability limits - Mina Kazemi; Sile Brennan; Vladimir Molkov (Fuel Processing Technology)
A Computational Fluid Dynamics (CFD) model is developed and validated against experimental data to predict the critical diameter and stability limits of non-premixed turbulent methane flames. The critical diameter defines the orifice size beyond which a stable flame persists at all driving pressures and below this pressure stability is pressure-dependent. Flame stability follows a “peninsula” curve of pressure versus release diameter, with sustained flames above the upper and below the lower pressure limits, while the intermediate region represents a blow-out zone where combustion is not sustained. The critical diameter, at the curve's rightmost point, is crucial for predicting sustained flames. Methane releases have been simulated for conditions in the region of the critical diameter, and for diameters and pressures ranging from 15 to 45 mm and 0.01 to 20 MPa, respectively, corresponding to the upper and lower flame stability limits using the realizable k − ε model and EDC combustion model. The simulations accurately captured blow-out and sustained flames, yielding a critical diameter of 42 mm, consistent with experiments. A methane flame at 5.88 MPa gauge through a 50 mm orifice was also simulated, showing flame length and lift-off distance in agreement with experimental observations. These results confirm the model's reliability in predicting methane flame stability, providing valuable insights for safety and combustion applications. This study presents the first CFD-based reproduction of the full methane flame stability curve, validating model reliability across a wide pressure range and providing a predictive tool for future applications, including the assessment of flame stability in methane‑hydrogen mixtures.